The revolution in systems engineering. - Hellestrand, G.R (IEEE spectrum)
The process of engineering systems on a chip will transform relationships among hardware, software, and mechanical designers. Various issues in systems engineering are discussed as is the role of systems engineering as a process. Co-design objectives and the state of co-design in electronic design automation are then considered as are virtual system prototypes